A suspensão do processo penal (artigo 366 do código de processo penal) e a reincidência - Brandão, Sonia Fátima (2007)
The work is based on the Brazilian Juridical system, the estate law of punishment, finds its legitimacy at the public utility, that is the reason why it demands conformation with the society, mutable during the time With the alteration of the article 366, of CPP, by the law 9.271/196, the new paragraph, refers only to, the hypothesis of arraigned defendant by edital that does not show up to court and that does not have a defense formed, will be proclaimed suspended from the process. As we know, the estate persecution activity must be practiced within a certain time gap. In case it exceeds its deadline regarding to the penal legislation, There will be an extinctive cause of the punishability called prescription. That is the article 366 of CPP, with the recent paragraphs, it declares that suspension of the process proclaimed by the incident of the enrolled request by the cited article, will not flow equally to prescription. We will show the changes that occurred at the juridical processual institute and its consequence of the new composition regarding to the article 366 of the CPP and also, the advantages and disadvantages that it brought to the penal processual system. The unstopable discussions about the occourred changes do not cause strengeness. It is public and notorious that changes provoque arrangements and disarrangements. The most relevant point that generated and still generates discussions of great importance is the theme referred to the prescribed dead line. It´s worth to protrude that when the promulgation of the law number 9.271/96, another question caused polemic - the retroactivity of the precept or not, now that the one itself presents the subject Penal Law, that allows the retroactivity of the new law, more benefic and also the subject Penal Processual Law in which the principle of the immediatism of the law is applied